Mutual Regulation of Receptor-Like Kinase SIT1 and B'κ-PP2A Shapes the Early Response of Rice to Salt Stress. Issue 9 (20th June 2019) - Zhao, Ji-Long; Zhang, Li-Qing; Liu, Ning; Xu, Shou-Ling; Yue, Zhi-Liang; Zhang, Lu-Lu; Deng, Zhi-Ping; Burlingame, Alma L.; Sun, Da-Ye; Wang, Zhi-Yong; Sun, Ying; Zhang, Sheng-Wei
Abstract : B'κ-PP2A positively regulates salt tolerance by limiting receptor-like kinase SIT1 activity in rice, while SIT1 phosphorylates B'κSer502 to enhance its protein stability. Abstract: The receptor-like kinase SIT1 acts as a sensor in rice ( Oryza sativa ) roots, relaying salt stress signals via elevated kinase activity to enhance salt sensitivity. Here, we demonstrate that Protein Phosphatase 2A (PP2A) regulatory subunit B'κ constrains SIT1 activity under salt stress. B'κ-PP2A deactivates SIT1 directly by dephosphorylating the kinase at Thr515/516, a salt-induced phosphorylation site in the activation loop that is essential for SIT1 activity. B'κ overexpression suppresses the salt sensitivity of rice plants expressing high levels of SIT1, thereby contributing to salt tolerance. B'κ functions in a SIT1 kinase-dependent manner. During early salt stress, activated SIT1 phosphorylates B'κ; this not only enhances its binding with SIT1, it also promotes B'κ protein accumulation via Ser502 phosphorylation. Consequently, by blocking SIT1 phosphorylation, B'κ inhibits and fine-tunes SIT1 activity to balance plant growth and stress adaptation.